# math

posted by .

Rewrite the equation so that y is the fucntion of x:

a. 1/7(49-7y)=5x-3y+14
b. 4(2x-3y)=-5(x+3y)

• math -

in the first, multiply each term by 7
49 - 7y = 35x - 21y + 98
14y = 35x + 49
y = (5/2)x + 7/2

the second is even easier, just expand, then re-arrange.

## Similar Questions

1. ### Calculus

How do I rewrite log4 1=0 as an equivalent exponential equation?
2. ### math

rewrite each equation as afunction of x.-3y+4y=11 Where are the equations?
3. ### algebra 116

Rewrite the equation y = 5x – 2 as a function of x. This problem is already a function of x. y = 5x - 2 as a function of x. Rewrite the equation –x – 4y = 20 as a function of x. Graph f(x) = –3x – 2. Solve the system by graphing.
4. ### Algebra I

Rewrite the equation so that y is the fucntion of x: a. 1/7(49-7y)=5x-3y+14 b. 4(2x-3y)=-5(x+3y) Can you please explain and show how to do these two problems?
5. ### Algebra I

Rewrite the equation so that y is the fucntion of x: a. 1/7(49-7y)=5x-3y+14 b. 4(2x-3y)=-5(x+3y)
6. ### Logarithms

Kepler's third law of planetary motion relates P, the period of a planet's orbit, to R, the planet's mean distance from the sun, through the equation log P = 1/2 (log k + 3 log R), where k is a constant. a) Rewrite the formula as a …
7. ### math

Rewrite the following equation in the center-radius form of the equation of a circle. x2 - 2x + y2 + 2y - 2 = 0
8. ### algebra

How do I rewrite this equation using radicals instead of rational exponents?
9. ### Math

Rewrite each equation below. Then solve your new equation. Be sure to check your solution using the original equation. (n+4)+n(n+2)+n=0
10. ### math

Can someone please check my work? Question~ Find the point-slope form of the equation that goes through these two points. (1, 20) and (8, 4.5) My Answer~ Y= y2-y1/x2-x1 (4.5-20)/(8-1) = -15.5/7 Rewrite -15.5/7 as (-15.5)/7 Rewrite

More Similar Questions